Contribuições da psicologia histórico-cultural para a pedagogia histórico-crítica - Martins, Lígia Márcia [UNESP] (My University, 2013)
This article aims to show elements based on historical-cultural psychology, which are reiterative of historically systematized scientific knowledge transmission as condition of human development and essential function of school education. In that way, it points the sign appropriation as decisive mark in the natural psychic basis overcoming towards to culturally established psychophysical properties formation, characterizing the psychism as an interfuncional system answerable for the constitution of the subjective image of objective reality. In the face of such presuppositions, it firms the role of school education in the mentioned image formation, highlighting the qualitative differences resultant of education based to quotidian and spontaneous concepts, as well as scientific ones. It pleads that the defense of sign quality offered to appropriation by school education is the main intersection point between the historical-cultural psychology and the historical-critical pedagogy.

Esse artigo tem como objetivo apresentar elementos fundamentados na psicologia histórico-cultural reiterativos da transmissão dos conhecimentos científicos historicamente sistematizados como condição de desenvolvimento humano e função precípua da educação escolar. Nessa direção, aponta a apropriação de signos como marco decisivo na superação das bases psíquicas naturais em direção à formação de propriedades psicofísicas culturalmente instituídas, caracterizando o psiquismo como sistema interfuncional responsável pela constituição da imagem subjetiva da realidade objetiva. Em face de tais pressupostos, afirma o papel da educação escolar na formação da referida imagem, com destaque às diferenças qualitativas resultantes do ensino pautado em conceitos cotidianos e espontâneos e em conceitos científicos. Advoga que a defesa da qualidade dos signos disponibilizados à apropriação pela educação escolar é o ponto de intersecção central entre a psicologia histórico cultural e a pedagogia histórico-crítica.
Contribuitions from historical-cultural psychology to historical-critical pedagogy
Keywords: Historical-Cultural Psychology; Historical-Critical Pedagogy; Psychic Development; Psicologia Histórico-Cultural; Pedagogia Histórico-Crítica; Desenvolvimento Psíquico